Pengolahan Secara Fisik Bahan Baku Pakan Ikan Sumber Nabati - Yuli Andriani; Rusky I. Pratama; Mochammad Naufal Ikmaludin; Rizky Ahmad Sudrajat; Yogi Fergiawan; Aisyah (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
The increasing demand and consumption of fish food from year to year means that demand for raw materials also increases. Vegetable raw materials can be an alternative because they have a relatively longer shelf life, are easy to find and are relatively cheap. Vegetable raw materials are raw materials that come from plants such as grains and nuts. Vegetable raw materials that exist in nature are usually reprocessed into feed with better nutritional content, so it is necessary to maintain the feed ingredients so that their content remains long-lasting. The raw materials used are soybeans, corn, sword beans, peanuts, kapok seeds and jackfruit seeds. Vegetable raw materials require physical processing to change texture, taste and other properties. Physical processing such as grinding, mixing, drying, soaking, steaming aims to increase nutrient availability, reduce anti-nutrients, extend the shelf life of vegetable raw materials, and improve the texture and taste of feed. Physical processing also plays a role in increasing the digestibility of vegetable ingredients, reducing the risk of microbial contamination, and extending the shelf life of fish feed. By optimizing physical processing techniques, plant feed can be produced that is efficient, high quality, and supports healthy growth and sustainable productivity of farmed fish. The use of vegetable raw materials for fish is starting to be widely used because it has good protein, for example the use of peanuts in fish feed which produces the best growth rate values, namely 0.7% and feed efficiency of 16.76%.